Analysis of the genetic diversity and structure of the Spanish apple genetic resources suggests the existence of an Iberian genepool. (18th October 2017) - Pereira‐Lorenzo, S.; Urrestarazu, J.; Ramos‐Cabrer, A.M.; Miranda, C.; Pina, A.; Dapena, E.; Moreno, M.A.; Errea, P.; Llamero, N.; Díaz‐Hernández, M.B.; Santesteban, L.G.; Laquidain, M.J.; et al.
Abstract: The nature and structure of genetic diversity in the Spanish apple germplasm preserved at the national level was widely unknown, since studies performed to date on this topic have been exclusively carried out at the regional scale. Here, 1453 accessions from Spanish collections of Malus × domestica were evaluated with a common set of 13 SSR (Simple Sequence Repeats) markers in order to estimate genetic diversity, to identify the underlying genetic structure and to unravel the relationships among them and among a wide set of international cultivars for reference. In total, 737 unique genotypes were identified, 581 diploids and 156 triploids. Using a model‐based Bayesian clustering procedure, two reconstructed populations were obtained for diploid genotypes; one retaining only Spanish cultivars (42% of genotypes), and a second containing all foreign cultivars the latter exhibiting evidence supporting the existence of a secondary sub‐structure. Similarly, analysis performed on the 156 triploid genotypes also revealed two reconstructed populations; one exclusively associated with local Spanish genotypes (44%). The Jaccard coefficient allowed clustering by UPGMA (Unweighted Pair Group Method) diploid and triploid genotypes, and remarkable differences in allelic composition among the different partitioning levels were found. AMOVA analyses showed moderate but significant differentiation among the main groups (0.08 ≤ F ST ≤ 0.12). Our results highlight an important fraction of the Spanish apple germplasm that constitutes a differentiated genepool with respect to the international and commercial apple cultivars. Moreover, the extent of the Spanish genetic diversity was spatially distributed along the northern Iberian Peninsula, suggesting an extensive migration of genotypes along the country. This study is the first valuable action for genetic conservation of apple at the national scale, and constitutes a decisive step towards the definition of a Spanish core collection that will be useful for further studies in dissecting the genetic control of important horticultural traits through genome‐wide association analysis in apple. Abstract : In this study, 1453 apple accessions were characterized with 13 SSR markers in order to evaluate the genetic diversity and to unravel the structure in the Spanish germplasm. 737 unique genotypes were identified (581 diploids and 156 triploids). Two reconstructed populations were obtained for diploid genotypes: one retaining only Spanish cultivars, and a second containing all foreign cultivars. For triploids, also two reconstructed populations were revealed, one exclusively comprising local Spanish genotypes. The results indicate that an important fraction of the Spanish apple germplasm constitutes a differentiated genepool with respect to the international and commercial apple cultivars.